2001
DOI: 10.1128/jb.183.13.4061-4070.2001
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Origin of Plant-Type 2-Keto-3-Deoxy- d - arabino -Heptulosonate 7-Phosphate Synthases, Exemplified by the Chorismate- and Tryptophan-Regulated Enzyme from Xanthomonas campestris

Abstract: Enzymes performing the initial reaction of aromatic amino acid biosynthesis, 2-keto-3-deoxy-D-arabinoheptulosonate 7-phosphate (DAHP) synthases, exist as two distinct homology classes. The three classic Escherichia coli paralogs are AroA I proteins, but many members of the Bacteria possess the AroA II class of enzyme, sometimes in combination with AroA I proteins. AroA II DAHP synthases until now have been shown to be specifically dedicated to secondary metabolism (e.g., formation of ansamycin antibiotics or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
64
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 36 publications
2
64
0
Order By: Relevance
“…However, CM0819 and DS2098 from C. glutamicum differ from the bifunctional CM from B. subtilis in that the former was more sensitive to chorismate regulation (this study) and the latter was more sensitive to prephenate regulation (Jensen & Nester, 1965). Previously, Gosset et al (2001) reported that DAHP synthase from Xanthomonas campestris was subject to allosteric inhibition by chorismate and was slightly inhibited by Trp. We found that DS2098 alone was not subject to inhibition by chorismate (this study) and was slightly inhibited by Trp (Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, CM0819 and DS2098 from C. glutamicum differ from the bifunctional CM from B. subtilis in that the former was more sensitive to chorismate regulation (this study) and the latter was more sensitive to prephenate regulation (Jensen & Nester, 1965). Previously, Gosset et al (2001) reported that DAHP synthase from Xanthomonas campestris was subject to allosteric inhibition by chorismate and was slightly inhibited by Trp. We found that DS2098 alone was not subject to inhibition by chorismate (this study) and was slightly inhibited by Trp (Liu et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This type of DAHP synthase is often involved in the biosynthesis of secondary metabolites, such as the ansamycin antibiotic rifamycin in A. mediterranei (Yu et al, 2001), phenazine in P. aureofaciens (Pierson et al, 1995), aurachin in Stigmatella aurantiaca (Silakowski et al, 2000), chloramphenicol in Streptomyces venezuelae (He et al, 2001) and ansatrienin and naphthomycin in Streptomyces collinus (Chen et al, 1999). In contrast, in Xanthomonas campestris a plant-type enzyme functions as the sole DAHP synthase supporting aromatic amino acid biosynthesis (Gosset et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the catalytic activity of DAH7PS has been shown to be an important mechanism for control of cellular levels of aromatic compounds in microorganisms and plants (3). 13 C NMR studies using whole cells of Escherichia coli have demonstrated that feedback inhibition of DAH7PS is the main mechanism for controlling carbon flow into the shikimate pathway (4). Different organisms employ various strategies for this feedback inhibition.…”
mentioning
confidence: 99%
“…This decoration of the barrel has been directly implicated in allosteric regulation of DAH7PS activity (8). DAH7PS enzymes have been divided into two types on the basis of protein size and amino acid sequence similarity (11): the smaller type I enzymes (30 -40 kDa), which can be further subdivided based on sequence into subtypes I␣ and I␤, and the larger type II enzymes (Ͼ50 kDa) (12,13). The sequence variability that defines the types and subtypes is directly paralleled in the structural variations that have been observed for DAH7PS enzymes (supplemental Fig.…”
mentioning
confidence: 99%